Maximising the use of municipal solid waste incineration bottom ash for sustainable and high-performance cementitious composites - Kailun Chen; Zhi Zhang; Fulin Qu; Bing Chen; Zhuo Tang; Wengui Li (Developments in the Built Environment)
Incorporating municipal solid waste incineration bottom ash (MSWI-BA) as fine aggregate into cementitious materials presents a promising pathway for sustainable construction and waste utilization. This study investigates the effects of MSWI-BA on mechanical performance, mass stability, and alkali-aggregate reaction (AAR) behaviour under various conditions. The results reveal a dual role of MSWI-BA: although higher contents intensify AAR, leading to alkali silica gel formation, crack propagation and strength loss, these drawbacks can be mitigated through careful optimization of particle size distribution and grading. Smaller particle sizes and finer gradations reduce stress concentrations and enable a more uniform distribution of reaction products, effectively lowering expansion rates. Removing reactive glass particles or substituting them with engineered glass aggregates further enhances material stability. Extensive alkali-silica gel formation and crack propagation are the primary factors contributing to strength reduction and expansion. Removing glass particles or replacing them with crushed glass significantly lessens the severity of AAR.